Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the equation of the tangent line to the function [tex]\( f(x) = x^2 - 3x + 5 \)[/tex] at the point [tex]\( (2, 3) \)[/tex], follow these steps:
### Step 1: Find the derivative of [tex]\( f(x) \)[/tex]
The derivative [tex]\( f'(x) \)[/tex] represents the slope of the tangent line at any point [tex]\( x \)[/tex].
Given the function:
[tex]\[ f(x) = x^2 - 3x + 5 \][/tex]
Its derivative is:
[tex]\[ f'(x) = \frac{d}{dx}(x^2 - 3x + 5) \][/tex]
[tex]\[ f'(x) = 2x - 3 \][/tex]
### Step 2: Evaluate the derivative at [tex]\( x = 2 \)[/tex]
To determine the slope of the tangent line at [tex]\( x = 2 \)[/tex]:
[tex]\[ f'(2) = 2(2) - 3 \][/tex]
[tex]\[ f'(2) = 4 - 3 \][/tex]
[tex]\[ f'(2) = 1 \][/tex]
So, the slope of the tangent line at the point [tex]\( (2, 3) \)[/tex] is 1.
### Step 3: Use the point-slope form to find the equation of the tangent line
The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( (x_1, y_1) \)[/tex] is the given point and [tex]\( m \)[/tex] is the slope.
Given:
- Slope ([tex]\( m \)[/tex]) = 1
- Point ([tex]\( x_1, y_1 \)[/tex]) = (2, 3)
Substituting into the point-slope form:
[tex]\[ y - 3 = 1(x - 2) \][/tex]
### Step 4: Simplify the equation of the tangent line
Solve for [tex]\( y \)[/tex] to put the equation in slope-intercept form ( [tex]\( y = mx + b \)[/tex] ):
[tex]\[ y - 3 = x - 2 \][/tex]
[tex]\[ y = x - 2 + 3 \][/tex]
[tex]\[ y = x + 1 \][/tex]
Therefore, the equation of the tangent line passing through the point [tex]\( (2, 3) \)[/tex] of the function [tex]\( f(x) = x^2 - 3x + 5 \)[/tex] is:
[tex]\[ \boxed{y = x + 1} \][/tex]
Hence, the correct answer is:
d. [tex]\( y = x + 1 \)[/tex]
### Step 1: Find the derivative of [tex]\( f(x) \)[/tex]
The derivative [tex]\( f'(x) \)[/tex] represents the slope of the tangent line at any point [tex]\( x \)[/tex].
Given the function:
[tex]\[ f(x) = x^2 - 3x + 5 \][/tex]
Its derivative is:
[tex]\[ f'(x) = \frac{d}{dx}(x^2 - 3x + 5) \][/tex]
[tex]\[ f'(x) = 2x - 3 \][/tex]
### Step 2: Evaluate the derivative at [tex]\( x = 2 \)[/tex]
To determine the slope of the tangent line at [tex]\( x = 2 \)[/tex]:
[tex]\[ f'(2) = 2(2) - 3 \][/tex]
[tex]\[ f'(2) = 4 - 3 \][/tex]
[tex]\[ f'(2) = 1 \][/tex]
So, the slope of the tangent line at the point [tex]\( (2, 3) \)[/tex] is 1.
### Step 3: Use the point-slope form to find the equation of the tangent line
The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( (x_1, y_1) \)[/tex] is the given point and [tex]\( m \)[/tex] is the slope.
Given:
- Slope ([tex]\( m \)[/tex]) = 1
- Point ([tex]\( x_1, y_1 \)[/tex]) = (2, 3)
Substituting into the point-slope form:
[tex]\[ y - 3 = 1(x - 2) \][/tex]
### Step 4: Simplify the equation of the tangent line
Solve for [tex]\( y \)[/tex] to put the equation in slope-intercept form ( [tex]\( y = mx + b \)[/tex] ):
[tex]\[ y - 3 = x - 2 \][/tex]
[tex]\[ y = x - 2 + 3 \][/tex]
[tex]\[ y = x + 1 \][/tex]
Therefore, the equation of the tangent line passing through the point [tex]\( (2, 3) \)[/tex] of the function [tex]\( f(x) = x^2 - 3x + 5 \)[/tex] is:
[tex]\[ \boxed{y = x + 1} \][/tex]
Hence, the correct answer is:
d. [tex]\( y = x + 1 \)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.